PERENCANAAN OVERLAY PADA LANDAS PACU DI BANDAR UDARA H.HASAN AROEBOESMAN ENDE - Fikri Irhamnan Ardiansyah; Wiwid Suryono; Vivi Rahmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The runway at H.Hasan Aroeboesman Ende Airport has dimensions of 1650m x 30m with flexible pavement. and a PCN value of 30 F/C/X/T. This study aims to plan a design mix formula to find the asphalt composition that meets the technical specifications required by the airport. From the results of determining the design mix formula, the asphalt used for planning runway overlays at H.Hasan Aroeboesman Ende Airport is 60/70 penetration asphalt with a content of 6.5% of the total hot mix asphalt and for aggregate with an amount of 93.5% of the total hot mix asphalt with aggregate gradation hot mix asphalt sieve 25 mm in the amount of 6%, 19 mm in the amount of 16%, 12.5 mm in the amount of 8%, 9.5 mm in the amount of 15%, 4.75 mm in the amount of 12%, 2.36 mm 11%, 1.18 mm 7%, 600 m 8%, 300 m 5%, 150 m 7%, and 75 m 5%. In planning the runway overlay with a thickness of 7.5 cm requires a cost of Rp. 4,131,060,000.00 (Four Billion One Hundred Thirty One Million Sixty Thousand Rupiah)